Transexualidade no ensino médio: discurso de coordenadores(as) e de professores(as) - Caparroz, Gustavo Oliveira (2023)
The term transsexuality was created to conceptualize and bring a definition to those people who do not fit the biologically determined standard. regarding the school environment. In this way, the present research is configured as a field study that proposes to analyze discourses on transsexuality, produced or reproduced by pedagogical coordinators and high school teachers. Objectives: (1) To problematize speeches in relation to transsexuality; (2) Understand how such speeches interfere in the work with transsexual students in the teaching-learning process. The methodological procedures consist of open interviews, consisting of a triggering question, transcription and content analysis The participants who constitute the sample are coordinators and teachers who work with students in high school and who made themselves available to give an interview related to their experience. The theoretical framework of this research is based on complex thinking and the theoretical categories analyzed are the operating principles, the imaginary complexes and the complex understanding of subjectivation in relation to stigma and prejudice. The research results show that subjectivity and imprinting marked by a long socio-historical-cultural process of marginalization of the LGBTQI community represent a strong barrier to the reception and understanding of transsexual students and the possible interference in learning.